2020
DOI: 10.1111/cob.12388
|View full text |Cite
|
Sign up to set email alerts
|

Eating in case of emotion dys‐regulation, depression and anxiety: Different pathways to emotional eating in moderate and severe obesity

Abstract: Summary Emotion dys‐regulation is thought to be involved in the development and maintenance of emotional eating (EE), notably through its links with anxious and depressive symptoms. AIM: The aims of the study were to: (a) examine the mediating effect of depressive and anxious symptoms on the relationship between emotion dys‐regulation and EE in obesity and (b) compare those links with various degrees of obesity severity. One hundred and twenty patients with obesity, including 60 with “n” (MO) (30 ≤ BMI < 40) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 68 publications
0
11
0
1
Order By: Relevance
“…Anxiety has shown a great effect on eating behavior [31,32] and has been proposed as a primary trigger for EE episodes [29]. High levels of anxiety or perceived stress have been found not only in people with obesity and with EE in weight loss treatment [69,70], but also in samples of college students [71]. Episodes of EE has been reported as the common response to anxiety [72], and it has been found a direct relation between anxiety and EE [18], and between anxiety and sweet craving (which has been associated with EE) [73] in a university population.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety has shown a great effect on eating behavior [31,32] and has been proposed as a primary trigger for EE episodes [29]. High levels of anxiety or perceived stress have been found not only in people with obesity and with EE in weight loss treatment [69,70], but also in samples of college students [71]. Episodes of EE has been reported as the common response to anxiety [72], and it has been found a direct relation between anxiety and EE [18], and between anxiety and sweet craving (which has been associated with EE) [73] in a university population.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was the development of psychometric assessment instruments that connected the gap between medical sciences (nutrition, epidemiology) and behavior science, and human food behavior could be better understood [11,13,32]. Using psychometric assessment instruments in clinical practice leads to a more patient-centered (individualized) approach to obesity management: for example, providing more psychological support to those who experience emotional eating [27,33], incorporating mindfulness techniques for those with external eating [34], or using restriction wisely as a strategy for weight loss [35]. Additionally, as behavioral factors influence food choice, but are also themselves influenced by the environment [7], using psychometric assessment instruments in epidemiological studies facilitate the approach of the problem of obesity using an ecological model [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated a direct relationship between emotional dysregulations and different types of psychopathology, such as substance abuse and eating disorders, depression, and particularly anxiety [ 16 , 17 , 18 , 19 ]. For example, research has shown that in health conditions associated with visual differences, such as that acne and severe obesity, emotional regulation has been shown to have moderate relationships to depression and moderate to strong relationships with anxiety [ 20 , 21 ]. However, the current literature lacks a specific and detailed assessment of ER difficulties and anxiety in patients with lipedema.…”
Section: Introductionmentioning
confidence: 99%